Breastfeeding support for working mothers : a literature review - Jusrawati; Suhartyny (Universitas Jenderal Achmad Yani Yogyakarta, 2025)
Background: Breastfeeding is essential for maternal and infant health. however, employed mothers face multiple workplace-related barriers. Insufficient support exacerbates the challenges, particularly for full-time working women, in maintaining breastfeeding practices.Aim: To analyse and evaluate the conceptual frameworks and physiological elements within existing research concerning breastfeeding support for employed women.Methods: This literature review utilised databases including PubMed, ScienceDirect, and EBSCO. An initial search yielded 1,583 titles, of which 8 articles met the inclusion criteria.Results: The findings indicate that successful breastfeeding among working mothers is influenced by institutional workplace support, maternal psychological conditions, knowledge of exclusive breastfeeding, partner perceptions and involvement, as well as technical barriers related to milk expression.Conclusion: There is a pressing need for breastfeeding support for employed mothers, encompassing workplace environment, family involvement, maternal attitudes, and knowledge. This review aims to inform future research and assess the extent of breastfeeding support available to working women